A review of research into business coaching supervision. Issue 2 (2nd July 2016) - Joseph, Stephen
ABSTRACT: A systematic search of the coaching literature for original peer-reviewed studies into business coaching supervision yielded seven research reports. Evaluation of these studies showed them to be low in the reporting of methodological rigour. However, as an emerging area of research with great importance for the development of the profession of business coaching these studies provide valuable insights into the functions of supervision and its benefits. Gaps in knowledge and directions for future research are identified. There is a need for future research to be more rigorous in its reporting of methods and analytic procedures, small-scale qualitative research that can provide insight into the issues and challenges of coaching supervision in specific contexts, and large-scale quantitative research which can provide broader and generalisable understandings into the uses and benefits of supervision.